UNDERSTANDING INDONESIAN CONSUMER’S INTENTION TO PURCHASE ORGANIC FOOD PRODUCTS: THE MODERATING ROLE OF PRICE SENSITIVITY - Ghaisa Marin Hartono; Alice Salendu; Eka Gatari (Jurnal Psikologi TALENTA, 2020)
As climate change is one of the major challenges of our time,  green products that benefit sustainable production, such as organic agriculture is not only a trend but a necessity. The purpose of this study was to investigate consumer’s value perceptions and their intentions to purchase organic food products. In addition, the study examined the moderating role of price sensitivity between perceived value and purchase intention. Survey data from 203 people in the Jabotabek were used to test our hypotheses, We found that only one value (emotional) had a significantly positive effect on organic food product purchase intention. The moderating effect of purchase experience was found only on the path between emotional value and organic food product purchase intention. The findings offer implications for academics, practitioners, and marketers in determining strategies that encourage people to purchase organic food products. We conclude that marketers should design strategies that maximize the emotional value of organic food products.